NAVIGATING CROSS-BORDER HEALTHCARE POLICIES AT THE SARAWAK–WEST KALIMANTAN BORDER - Eva Novianty Rachmat; Dolly Paul Carlo; Helmy Hazmi (Universitas Airlangga, 2026)
Introduction: Access to healthcare remains a challenge for the Sarawak–West Kalimantan border communities. The close proximity to neighbouring countries and uneven healthcare infrastructure often lead these communities to seek care across the border. A previous study revealed that nearly 60% to 70 % of Malaysia’s incoming patients came from Indonesia. Aims: This study aimed to identify and compare the characteristics of Malaysia’s and Indonesia’s healthcare access policies related to Sarawak–West Kalimantan border communities. Methods: This study employed a qualitative phenomenological approach and conducted semi-structured, in-depth interviews with 40 participants, including government officials, community leaders, and residents from 12 locations along the border. Data collection was conducted between October 2023 and May 2024, and the collected data were analysed through inductive thematic analysis. Results: Healthcare mobility between Sarawak and West Kalimantan relies on informal community trust over standardized frameworks. Malaysia’s institutionalized outreach contrasts with Indonesia’s army-assisted delivery and insurance schemes. Divergent border procedures and non-binding bilateral platforms like Sosek Malindo further limit effective cooperation, highlighting a significant lack of harmonized enforcement and policy integration. Conclusion: Sustainable cross-border healthcare governance requires formalised bilateral standard operating procedures encompassing emergency mobility, disease surveillance, and referral systems, complemented by active community involvement. Strengthening these mechanisms would transform cross-border healthcare from an informal, ad hoc practice into an institutionalised framework that ensures equitable and continuous care for border communities.